The Effectiveness of Butterfly Hug in Reducing Anxiety Long-Distance Relationship (LDR) with Parents in Nursing Students - Caturini, Endang; Safitri, Nastiti Dyah; Sugi, Sugiyarto (Future Science, 2023)
Introduction: Anxiety related to a long-distance relationship with parents is an unpleasant emotional reaction when away from parents that can cognitively interfere with feelings and emotions caused by feelings of loneliness and longing for home. One of the ways to reduce anxiety is a butterfly hug. Methods Using quasi-experimental with the control group and pre-posttest design. The sampling technique used purposive sampling. The sample consisted of 60 respondents divided into a control group of 30 respondents and an intervention group of 30 respondents. Using the Zung Self-Anxiety Rating Scale for the instrument. The intervention group received a butterfly hug for 6 days in 8 sessions every day, and the control group received music therapy for 6 days. Bivariate analysis used the parametric test paired sample t-test to see the difference between the prepost-test intervention group and to see the difference between the prepost-test control group on the anxiety level using the nonparametric Wilcoxon test. Analysis of bivariate test to see the difference between groups using the independent sample t-test. Result: The results of the Wilcoxon test of the anxiety level control group p=0,274 (p=>0,05), meanwhile the results of the intervention group of the paired sample t-test intervention group there was a significant effect (p=0,000). The results of the independent sample t-test between the control and intervention groups were p=0,001 (p=<0,05). Conclusions: Butterfly hug therapy is an effective therapy to reduce anxiety in LDR with parents in nursing students. This therapy is expected to be applied and used as an intervention to reduce anxiety.